2017
DOI: 10.1093/jxb/erx111
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide changes in microRNA expression during short and prolonged heat stress and recovery in contrasting rice cultivars

Abstract: HighlightHeat susceptible and tolerant rice genotypes have different landscapes of miRNAs and the tolerant genotypes show efficient recovery mediated by miRNAs. Roots regulate miRNAs more sensitively than shoots during heat stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 60 publications
3
97
0
Order By: Relevance
“…3b), implying their involvement in BPH response. In addition, miR1859 showed higher expression during heat stress treatment [22]. Members of the miR1861 family regulate starch accumulation and yield in rice [21], whilst miR390-TAS3-ARFs forms an auxin-responsive regulatory network controlling root growth [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3b), implying their involvement in BPH response. In addition, miR1859 showed higher expression during heat stress treatment [22]. Members of the miR1861 family regulate starch accumulation and yield in rice [21], whilst miR390-TAS3-ARFs forms an auxin-responsive regulatory network controlling root growth [20].…”
Section: Discussionmentioning
confidence: 99%
“…2a), many of which belonged to known miRNA families including miR156, miRNA160, miR166, miR169, miR1846, miR1861 and miR319 (Additional file 3: Table S2). Members of the miRNA families were reported to be involved not only in growth, development, grain size and hormone signaling, but also in response to biotic and abiotic stress [21][22][23][24][25][26][27][28][29][30][31]. These BPH6 responsive DEMs might be involved in response to BPH.…”
Section: Identification Of Mirnas Related To Bph Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that the lower molecular weight polypeptide decreased with the increase of storage time, while the higher molecular weight polypeptide increased (Park et al, 2012;Chrastil, 1990). More importantly, the content of acetic acid soluble protein in milled rice decreased during 7 years of storage (Bolling et al, 1977;Bolling et al, 1978;Mangrauthia et al, 2017). During the aging process, the protein content of rice grain changed slightly, but the soluble nitrogen decreased continuously.…”
Section: Effects Of Rice Aging On Physicochemical Properties Of Storamentioning
confidence: 91%
“…miRNAs, small endogenous non-coding RNAs of 19-25 nucleotides, have emerged as ubiquitous critical regulators in nearly all eukaryotes and are considered important modulators of gene expression at the post-transcriptional level, either directing the cleavage of target genes or inhibiting translation. Consequently, miRNAs play an essential role in plant response to a number of environmental stresses, including plant acquisition of heat tolerance (Mangrauthia et al, 2017). In turn, PAP has been shown to be a retrograde inhibitor of the nuclear XRN exoribonucleases, thus protecting primary miRNAs from being degraded and therefore promoting mature miRNA production.…”
Section: Previewsmentioning
confidence: 99%